Harina de plátano como sustituto de grasa en salchicha de pollo y efecto sobre las propiedades funcionales y organolépticas - Álvarez Bermúdez, Mary Gabriela (2017)
Sausage is defined as a mixture of meat, fat, salts and spices that are introduced into artificial casings and subjected to a cooking process, followed by storage at low temperatures. The purpose of the present work was to evaluate the effect of banana flour in the functional and organoleptic properties of a chicken sausage by replacing fat with banana flour, which was used in two ways: with peel and without it respectively. For the effect, six combinations with different percentages were formulated, obtaining the following treatments T1 (2% type 1 flour), T2 (4% type 1 flour), T3 (6% type 1 flour), T4 (2% type 2 flour), T5 (4% type 2 flour), T6 (6% type 2 flour), additional to an absolute control of a commercial nature formulated by ingredients used in a common chicken sausage, in this research an experimental unit of 4 kg of base paste was used. Analysis of functional CRA (water retention capacity), PPC (weight loss per cooking) and organoleptic (appearance, consistency, texture, color, smell, taste), the data obtained were analyzed using the statistical program ssps version 21. As a result, the best treatment is T6 (type 2 flour at 6% substitution), because there was no effect on the properties and the cost was reduced by $ 0.30 compared to the traditional sausage cost, improving the profitability of the product.